Influence of CNC turning variables on high strength Beryllium-Copper (C17200) alloy using tungsten carbide insert. (2020) - Alagarsamy, S.V.; Ravichandran, M.; Meignanamoorthy, M.; Chanakyan, C.; Dinesh Kumar, S.; Sakthivelu, S.
Abstract: The current investigation is, to determine the optimum process variables on CNC turning operation of Be-Cu (C17200) alloy using grey relational approach (GRA). In GRA, optimum level of turning variables can be identified by the grey relational grade as the performance index. In present work, the three turning variables were chosen namely cutting speed (V1  = 800 rpm, V2  = 1000 rpm and V3  = 1200 rpm), feed rate (F1  = 0.10 mm/rev, F2  = 0.12 mm/rev and F3  = 0.14 mm/rev) and depth of cut (D1  = 0.8 mm, D2  = 1.0 mm and D3  = 1.2 mm) and the output responses such as material removal rate (MRR) and surface roughness (SR) were considered. A grey relational grade attained from the GRA was used to identify the optimum turning process variables on multi response characteristics with an objective to maximize the MRR and minimize the SR. Based on the grey relational grade, optimum level of turning variables was identified as V3 F3 D2 that is cutting speed at level 3 (1200 rpm), feed rate at level 3 (0.14 mm/rev) and depth of cut at level 2 (1.0 mm). The significant effect of each variable on response was determined by analysis of variance (ANOVA). From ANOVA result shows that cutting speed was the most significant factor on multi response characteristics followed by depth of cut. Finally, the verification test was performed to validate the experimental results.